الولادة الطبيعية بعد سوابق القيصرية الواحدة المجراة منذ سنة ونصف أو أقل - عبد الرحمن أحمد; الدالي عصام; يونس نِعَم محمد (Latakia University Journal -Medical Sciences Series, 2019)
أجري البحث في مشفى الأسد الجامعي باللاذقية في الفترة بين 1/1/2003 و30/6/2004 وشمل 138 حاملا مع سوابق قيصرية واحدة منذ سنة ونصف أو أقل, أجري ل 30 مريضة قيصرية انتخابية وتعرضت 108 مريضات لتجربة مخاض وبدارسة سير المخاض وطريقة الولادة عند هذه الفئة تبين ما يلي: بلغت نسبة الولادة الطبيعية (المهبلية) لسوابق القيصرية: 62.2% في حال تعرضها لمخاض . 40.6% عندما كان الحوض غير مجرب . 66.6% عندما كان الحوض مجربا. 77.7% تم تحريض المخاض بالأوكسيتوسين. 63.6% تم تنظيم المخاض بالأوكسيتوسين. حوض غير مجرب. جنين عرطل. مجيء معيب. حمل متعدد. الاستطباب السابق للقيصرية الأولى معاود. لم تلاحظ أي حالة تمزق ندبة عقب الولادة المهبلية لسوابق القيصرية. لم يجر أي استئصال رحم ولادي ولم تحدث أية وفاة والدية أو جنينية بسبب تمزق ندبة القيصرية. يعتبر كل من العوامل التالية ذا إنذار غير جيد بالنسبة للولادة المهبلية لسوابق القيصرية : The research was conducted in AL ASSAD hospital university in Lattakia between 1/1/2003 – 30/6/2004 and included 138 pregnant women with one previous cesarean section since one year and a half or less 30 patients had cesarean section. (108) patients experienced labor while the other (30) were subjected to selective cesarean. - The study of labor mechanism and delivery way on that group of pregnants has releaved the following : - rate of vaginal delivery with one previous cesarean section was : 62.2% in case of exposure to labor. 40.6% when pelvis inexperienced. 66.6% when pelvis experienced 77.7% had induction of labor with oxcytocin 63.6% had stimulation of labor with oxcytocin. There was not any case of scar rupture post vaginal delivery with one previous cesarean section. There was no cesarean hysterectomy maternal mortality or fetal mortality happened due to scar rupture. The following factors are considered bad prognosis for vaginal delivery with one previous cesarean section: inexperienced pelvis large fetus abnormalities in presentation multi fetal pregnancy repeated indication of cesarean section